ZOONOTIC MALARIA POTENTIAL IN PAPUA FROM THE PERSPECTIVE OF ONE HEALTH AND NATIONAL RESILIENCE - Annisa Putri Cahyani; I Putu Juli Sukariada; Eni Susanti; Hendro Sukoco; Dwi Nurhayati; Aven B Oematan (Pena Cendekia Insani, 2025)
Malaria remains a major public health burden in Indonesia, with Papua contributing the highest incidence nationally. Recent ecological changes, increasing human–wildlife interaction, and expanding vector habitats have raised concerns about the potential emergence of zoonotic malaria in the region. This study aims to analyze the potential risk of zoonotic malaria in Papua through a One Health perspective and assess its implications for national resilience. A descriptive qualitative literature review was conducted using scientific publications from the last five years, WHO reports, and national malaria surveillance data. Findings indicate that ecological disturbances, deforestation, and occupational exposure in forested areas increase the likelihood of spillover involving Plasmodium species such as P. knowlesi and P. cynomolgi. Limited healthcare access, high population mobility, and persistent transmission further exacerbate vulnerability. The potential emergence of zoonotic malaria poses multidimensional threats to Indonesia’s national resilience, particularly in the domains of food security, economic stability, social cohesion, and national security. Strengthening integrated surveillance, enhancing diagnostic capacity, improving environmental management, and promoting cross-sectoral collaboration are essential strategies to mitigate zoonotic malaria risks in Papua. This study highlights the importance of adopting a One Health approach to support malaria elimination efforts and safeguard national resilience